Financing Innovation - Yoo, JaeHoon (World Bank, Washington, DC, 2012)
More than 24 countries operate separate boards and exchanges aimed at small and medium-size enterprises (SMEs). Equity markets play a critical role in fostering economic productivity by financing innovation. But only a few SME exchanges function properly, providing coveted fresh capital and liquidity. What steps are key to building an efficient exchange to provide risk capital for SMEs? Creating an SME-friendly market architecture supported by effective institutions and forging links to policies that foster a new class of investable equities.